Elasticity of consumer demand: estimation using a Quad- Ratic Almost Ideal Demand System - Gostkowski, Michał (Elastyczność popytu konsumpcyjnego: estymacja na podstawie Quadratic Almost Ideal Demand System, 2018)
This paper analyzes consumer demand using a Quadratic Almost Ideal Demand System (QUAIDS), which is an extension of an Almost Ideal Demand System (a complete demand system). Complete demand system models can be used to find the relationships that are impossible to discover using single-equation models. Additionally, the QUAIDS model can be used to model a nonlinear Engel curve. The research was based on household microeconomic data collected by GUS (the Polish Central Statistical Office) in the period 1999-2015. The complete demand model has been extended by demographic variable. The results show that the QUAIDS model does not reduce to the AIDS model and is an adequate tool to analyze consumer demand
Econometrics = Ekonometria, 2018, Vol. 22, No. 1, s. 68-78
Keywords: complete demand system; Quadratic Almost Ideal Demand System; QUAIDS; elasticity of demand; kompletny model popytu; elastyczność popytu